Professional development through mutually respectful relationship: senior teachers' learning against the backdrop of hierarchical relationships. Issue 1 (1st January 2019) - Hargreaves, Eleanore; Elhawary, Dalia
ABSTRACT: This article draws on interview data across eight months from senior teachers (i.e. experienced teachers who are subject leaders) in Egyptian primary schools, to explore how they described their learning during a professional development project in which they led gatherings of interested teachers in teacher learning communities. The article explores the hypothesis that an important ingredient for effective teacher professional development is an affirming relationship between the learning-teacher and their coach or peers. Carl Rogers' person-centred theory from the psychotherapy context is explored here in an educational context where, as in many countries, hierarchical relationships control how professionals relate to each other and express themselves. The article concludes that an enhanced sense of professional value and authority can result from more mutually respectful relationships and become the bedrock for significant professional development.